Efecto de la coinoculación de Beauveria bassiana e Isaria fumosorosea sobre la viabilidad de larvas de Spodoptera eridania en condiciones de laboratorio. - BENITES AMAYA, Katherine Brigith (2019)
The effect of the coinoculation of Beauveria bassiana and Isaria fumosorosea on the viability of Spodoptera eridania larvae under laboratory conditions was evaluated. For which the larvae of S. eridania in larval stage I were raised; to each treatment (10 larvae) it was applied by aspersion the suspensions of B. bassiana, I. fumosorosea; and B. bassiana and I. fumosorosea at the concentration of 1 x 106 conidia / mL, likewise, a control consisting of 0.1% Tween 80 was applied. The readings were made every 24 h, registering symptoms and/or signs such as decreased movement, dehydration, melanization and mortality. The dead larvae were put in humid chambers in order to observe the growth of the mycelium and confirm that the death of the larva was caused by the fungi evaluated. It was obtained that the percentages of viability of larvae of S. eridania showed a significant difference between the treatment of B. bassiana and I. fumosorosea (26.7%), with the treatment of B. bassiana (56.7%) and with the treatment of I. fumosorosea (60.0%), indicating a better performance in its entomopathogenic activity compared to its effect individually._x000D_ It concluded that the effect of the coinoculation of B. bassiana and I. fumosorosea significantly decreases the viability of S. eridania larvae, under laboratory conditions.